2022
DOI: 10.1002/ijc.34048
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2: The diversity of pathological effects in tumorigenesis and immune response

Abstract: Annexin A2 (ANXA2) is widely used as a marker in a variety of tumors. By regulating multiple signal pathways, ANXA2 promotes the epithelial‐mesenchymal transition, which can cause tumorigenesis and accelerate thymus degeneration. The elevated ANXA2 heterotetramer facilitates the production of plasmin, which participates in pathophysiologic processes such as tumor cell invasion and metastasis, bleeding diseases, angiogenesis, inducing the expression of inflammatory factors. In addition, the ANXA2 on the cell me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 164 publications
0
21
0
Order By: Relevance
“…Currently, the physiological role of OBPs is not fully understood [35] , and perhaps the urine proteome can play a role in exploring the specific mechanism of action of OBPs. Annexin A2 is widely used as a marker for a variety of tumors [36] . In addition, László ZI et al showed that neurocadherin is one of the most important cell adhesion molecules during brain development and plays an important role in neuronal formation, neuronal proliferation, differentiation and migration, axonal guidance, synaptogenesis and synaptic maintenance [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the physiological role of OBPs is not fully understood [35] , and perhaps the urine proteome can play a role in exploring the specific mechanism of action of OBPs. Annexin A2 is widely used as a marker for a variety of tumors [36] . In addition, László ZI et al showed that neurocadherin is one of the most important cell adhesion molecules during brain development and plays an important role in neuronal formation, neuronal proliferation, differentiation and migration, axonal guidance, synaptogenesis and synaptic maintenance [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Annexins display different expression patterns in bladder cancer and play an essential role in the pathogenesis by triggering various downstream signaling pathways and functional regulatory effects [ 19 , 20 , 43 , 44 , 45 , 46 , 47 , 48 ]. Increasing evidence indicates that AnxA2 is upregulated in several types of human cancer [ 13 , 17 , 21 , 22 , 24 , 26 , 27 , 28 , 29 ]. Annexin A2 is a potential biomarker for predicting drug resistance and recurrence of bladder cancers [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of AnxA2 has been observed in gastric cancer, endometrial cancer, pancreatic ductal adenocarcinoma, hepatocellular carcinoma, breast cancer, kidney renal clear cell carcinoma, high-grade prostate cancer, and glioblastoma. It has a significant correlation with advanced stage and unfavorable prognosis [ 13 , 17 , 21 , 22 , 24 , 26 , 27 , 28 , 29 ]. Previous studies suggested that AnxA2 was upregulated in bladder urothelial carcinoma tumor tissues and associated with lymph node metastasis and distant metastasis [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin A2 (ANXA2) is a calcium-dependent phospholipid binding protein and regulates cellular growth ( Hajjar and Krishnan, 1999 ; Wang and Lin, 2014 ). ANXA2 is involved in various pathophysiological processes, including epithelial-mesenchymal transition, fibrinolysis and cancer drug resistance ( Wang et al, 2019 ; Huang et al, 2022 ). In vitro , ANXA2 promoted migration and invasion of esophageal squamous carcinoma cells by activating the MYC-HIF1A-VEGF signaling cascade ( Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%